O desenvolvimento saudável da criança de 0 a 24 meses segundo Emmi Pikler - Gomes, Erily Eriane Souza Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In this scientific paper, we'll discuss what should be the healthy development of a child according to Emmi Pikler, answering the following questions: How does the healthy development of a child occur? and What is the contribution of Pikler to daycare practices?. To answer those questions, we had carried out a qualitative bibliographical data survey in order to deal with the theme. We realizedthat this subject is little addressed, but gradually is gaining space in the field of research. In addressing this issue, we want to highlight how the natural development of a child occurs, and what practice the educator must adopt so that it does not bring losses. Pikler's approach is about respect, freedom and autonomy of a child, promoting health, physical, affective and emotional well-being, without the need for direct educator mediation. In this way the role of the adult is: to create an adequate space so that the child can have its autonomy; to build affective bonding in a way that it will bring security; and to have a watchful eye for all their needs

Neste trabalho de conclusão de curso, abordaremos o desenvolvimento saudável da criança segundo Emmi Pikler, respondendo as seguintes questões de pesquisa: como se dá o desenvolvimento saudável da criança? e qual a contribuição de Pikler para as práticas na creche?. Para isto, foi realizado um levantamento de dados de abordagem qualitativa, do tipo bibliográfico, que tratassem do tema. Percebemos que o desenvolvimento saudável da criança é um assunto pouco abordado, mas aos poucos está ganhando seu espaço no campo de pesquisa. Ao tratarmos deste tema, queremos evidenciar como ocorre o desenvolvimento natural da criança e qual a prática que o educador deve adotar para que não traga prejuízos globais a ela. A compreensão da abordagem de Pikler relaciona-se ao respeito, liberdade e autonomia da criança, promovendo saúde, bem-estar físico, afetivo e emocional, sem a necessidade de uma mediação direta do educador. Desta forma o papel do adulto é criar um espaço adequado para o movimento e autonomia da criança, construindo vínculo afetivo de forma que traga segurança, e ter um olhar atento para todas as suas necessidades
Keywords: Nemzetközi Pikler Emmi Közalapítvány Pikler Intézet (Budapeste, Hungria); Educação - Estudo e ensino; Saúde - Desenvolvimento; Cuidados; Lactente; Education - Study and teaching